Live Worksheets Media to Improve Exploration of Dance Movements of Grade II Elementary School Students - Husnawati, Riska Nidaul; Nurharini, Atip (Journal of Education Technology, 2024)
One important aspect of dance education is the exploration of dance movement, which not only builds motor skills but also provides a platform for developing students' identity and emotional expression. This research aims to develop E-LKPD based on Live worksheets to increase students' exploration of dance movements. The subjects of this research were material experts, media experts, class II teachers, and 25 class II students. This type of research is Research and Development (RnD) using the ADDIE model. The data collection methods for this research are observation, interviews, questionnaires, documentation, and tests. The data analysis technique is qualitative and quantitative descriptive analysis. Quantitative data can be in the form of an increase in the average learning outcomes of dance movement exploration which can be calculated using the N-Gain Test. The research results were that the validation test by teaching materials experts was 95% with very feasible criteria, and the validation test by media experts received a score of 97% with very feasible criteria. The N-gain test results show a value of 0.7, meaning it has high criteria. Live worksheets-based E-LKPD teaching materials are feasible and effective for increasing movement exploration for second-grade elementary school students. E-LKPD teaching materials are flexible and efficient to use.